Morphological variation of Rumex longifolius DC. in the Alps and mountains bordering Bohemia - Sonnberger, Bernd (Biodiversity: Research and Conservation, 2024)
Neophytic populations of Rumex longifolius (northern dock) in the Alps and the mountain ranges bordering Bohemia were investigated to compare the length-width ratio of the basal leaf blades, the shape and size of the valves (fruiting inner perianth segments), and the tendency to develop tubercles on the valves. Five populations from the Czech Republic (Krkonoše mountains and Mount Ještěd), Germany (Bavarian Forest), Austria (Arlberg Pass), and Switzerland (Engadin) were described by quantitative evaluation of specimens collected in 2014-2018 and their offspring cultivated in the Botanical Garden of Frankfurt am Main for 2 growing seasons. Results of this study indicate that the populations probably originated by discrete introduction events. The Engadin population shows features of introgression with Rumex crispus. Probably R. longifolius is native here, but there is indirect evidence only. The morphology of specimens from the upper Tyrolian Inn valley in the herbarium of the Natural History Museum Vienna suggests their origin from the Engadin, which should be confirmed statistically by further collections. The taxonomical significance of subsp. sourekii Kubát, described on the basis of a single character (leaf shape), is questioned because of the polymorphism of the species, and the correlation of leaf width with age and vigour, observed in the cultivation experiments. The morphological variability and ecological preferences of R. longifolius suggest its probable hybrid origin from R. aquaticus and R. crispus.